Ergonomia aplicada na redução da dor lombar em ciclistas com o suporte da eletromiografia - Macedo, Regina Moreira Borges de (2014)
One of the applications of ergonomics is the prevention of musculoskeletal disorders, among which the low back pain is one the most prevalent. Pedaling isn’t a natural movement in the human ergonomics and, consequently irregularities in the positioning leads to imbalances. The inappropriate posture changes the characteristics of muscle recruitment, especially in the lumbar region and lower limbs during the act of cycling, which makes relevant the investigation of complaint of pain and discomfort in the spine. The objective of this study was to analyze the impact of ergonomic adjustments in man-bike system in low back pain of cyclists, from electromyographic records. For this, a descriptive study of 35 cyclists evaluated three protocols for adjusting the saddle height: (a) a protocol of reference (REF), saddle height initially presented by the athlete;(b) P1 based on Burke, related to the crotch height multiplied by the constant 1.09; (c) P2 where the seat height is adjusted by knee flexion when the pedal is in the lower part of the pedal cycle (PMI). All protocols were evaluated using electromyography (EMG System of Brazil, model 1600-U12) of the quadratus lumborum muscles, erector lumbar spine, thoracic spine erector, rectus abdominis, rectus femoris, vastus lateralis, vastus medialis, hamstrings, gastrocnemius . Additionally, the geometry of the angular positioning of the joints of the lower limbs during pedaling was evaluated by means of photogrammetry, where were measured angles of movement of the ankle, knee and hip in two phases of the pedaling cycle: (1) the upper motor point (SMP), and (2) the PMI.The impact of the recommendations was evaluated before adjustment and 30 days and 5 months after the ergonomic recommendation by applying visual analogue pain scale. Results showed a significant reduction in reported pain after adjustments at 30 days (p = 0.000), which lasted until 5 months (p = 0.023).In the electromyography comparison of muscle recruitment between the protocols were found: (1) between REF and P1, a significantly lower level of muscle recruitment for: lumbar (p = 0.006), posterior lower limb (p = 0.003) and abdominal (p = 0.002), (2) between REF and P2, significantly less muscle recruitment in the abdominal region (p = 0.009), (3) between P1 and P2, reduced muscle recruitment for subsequent lower limb in P1 (p = 0.030). The analysis of the movement geometry, significant differences for the knee angle of PMS (p = 0.003) and PMI (p = 0.012) P1 only. From these results, the initial study hypothesis was confirmed, since the mean signal of the EMG tracing, was effective in quantifying changes in specific muscle recruitment of the sport, for the different methods of adjusting the saddle, and served as basis for the recommendation of ergonomic adjustments, since it was after them, was decreased muscle overload in the lumbar region. The evidence allowed to conclude that P1 was the most effective protocol in ergonomic tuning recommendation of the saddle, and the same can be the reference of recommendation for athletes in the same cycling conditions anthropometric and training like on this studied here. It has been possible to establish that recruited more muscles electromyography should be the focus of strength training, the preparation of athletes in order to decrease the biomechanical risk for developing injuries during training and competitions.